Peran Diet Kalium sebagai Pencegahan Resistensi Insulin - Pramastha Candra Sasmita; ade yonata; TA Larasati (CV. Jasa Sukses Abadi, 2021)
The incidence and prevalence of type II diabetes is increasing worldwide that makes clinicians must try to identify, prevent, and treat patients appropriately. Diabetes mellitus is divided into 2 types, namely type I and type II. Type I diabetes mellitus occurs genetically because the body cannot produce insulin, while type II diabetes mellitus occurs due to acquired insulin resistance. Diabetes mellitus is a group of metabolic disorders with manifestations of hyperglycemia due to damage to pancreatic cells that causes insulin deficiency (type I diabetes) to insulin resistance (type II diabetes). High levels of potassium in the blood can help increase insulin secretion in pancreatic cells through a membrane potential that triggers depolarization, so that the sensitivity of β cells to the incidence of hyperglycemia increases. Potassium intake is very important in helping to increase insulin secretion of pancreatic cells so as to prevent hyperglycemia and reduce the risk of insulin resistance. Potassium as an electrolyte in the body, both serum levels and dietary intake are associated with the incidence of diabetes. Lower potassium levels have been found to be associated with an increased risk of diabetes in several studies.